2015
DOI: 10.1177/0269216315583032
|View full text |Cite
|
Sign up to set email alerts
|

Dying in the hospital setting: A systematic review of quantitative studies identifying the elements of end-of-life care that patients and their families rank as being most important

Abstract: Background:The majority of expected deaths occur in hospitals where optimal end-of-life care is not yet fully realised, as evidenced by recent reviews outlining experience of care. Better understanding what patients and their families consider to be the most important elements of inpatient end-of-life care is crucial to addressing this gap.Aim and design:This systematic review aimed to ascertain the five most important elements of inpatient end-of-life care as identified by patients with palliative care needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
256
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(289 citation statements)
references
References 30 publications
22
256
2
2
Order By: Relevance
“…Research on family members in acute-care settings mainly concerns problems experienced by family members, e.g., experience of patients’ symptom burden and management, communication and relationships with professional caregivers, involvement in decision making, or their own needs for care (Robinson, Gott, & Ingleton, 2014; Steinhauser, Voils, Bosworth, & Tulsky, 2015; Virdun, Luckett, Davidson, & Phillips, 2015). The tendency to focus on life-sustaining treatment may encourage a disengagement from, and diminish recognition of, the acute-care environment as a setting for EoL care (Bloomer et al, 2013; Chan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research on family members in acute-care settings mainly concerns problems experienced by family members, e.g., experience of patients’ symptom burden and management, communication and relationships with professional caregivers, involvement in decision making, or their own needs for care (Robinson, Gott, & Ingleton, 2014; Steinhauser, Voils, Bosworth, & Tulsky, 2015; Virdun, Luckett, Davidson, & Phillips, 2015). The tendency to focus on life-sustaining treatment may encourage a disengagement from, and diminish recognition of, the acute-care environment as a setting for EoL care (Bloomer et al, 2013; Chan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that the four most important elements of end-of-life hospital care identified by inpatients and families in a recent systematic review are also relevant to the ICU setting (Virdun et al, 2015). The patients' and their families' wishes are: effective communication; expert care; respectful and compassionate care; and trust and confidence in clinicians (Virdun et al, 2015).…”
Section: Concept Of "Good Death"mentioning
confidence: 99%
“…It is conceivable that the four most important elements of end-of-life hospital care identified by inpatients and families in a recent systematic review are also relevant to the ICU setting (Virdun et al, 2015). The patients' and their families' wishes are: effective communication; expert care; respectful and compassionate care; and trust and confidence in clinicians (Virdun et al, 2015). Within the context of ICU, a good death is achievable when ICUs adopt the principles of a palliative approach and the ICUs team communicates with patients and families and involves them in patient-focussed end-of-life care decision-making (Fonseca et al, 2012, Cook andRocker, 2014).…”
Section: Concept Of "Good Death"mentioning
confidence: 99%
“…Virdun et al 9 in this journal have shown in their systematic review that there is no surprise about the things that matter to dying patients and their families -effective communication, expert and kind care and perhaps really importantly, trust and confidence in those looking after them.…”
mentioning
confidence: 99%
“…Palliative Medicine 29 (9) But good stories encourage us. Julie Myerson, 27 novelist, described her mother-inlaw's death: Sandwiches were eaten, there was laughter, teasing, backchat.…”
mentioning
confidence: 99%